2014
DOI: 10.1186/1472-6963-14-126
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric testing of a scale assessing the sharing of medical information and interprofessional communication: the CSI scale

Abstract: BackgroundInterprofessional collaboration is essential in creating a safer patient environment. It includes the need to develop communication and coordination between professionals, implying a better sharing of medical information. Several questionnaires exist in the literature, but none of them have been developed in the French context. The objective was to develop and test the psychometric properties of the communication and sharing information (CSI) scale which assesses specifically interprofessional commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
0
15
1
1
Order By: Relevance
“…We could argue there lies a possible relation in the average duration of maternity care assistance and the midwives' satisfaction with collaboration with MCA(O)s on the level of urbanisation in our study. Our study did not find predicted associations of satisfaction with collaboration with attitudes towards work, such as job satisfaction, turnover intentions or retention (Baggs and Ryan, 1990;Chang et al, 2009;Anthoine et al, 2014;Zhang et al, 2016). Instead, we found differences on work-related and personal characteristics with some care providers, on the level of urbanisation, region, age, working years, non-Dutch origin and problems of accessibility in the interaction.…”
Section: Synopsiscontrasting
confidence: 95%
See 1 more Smart Citation
“…We could argue there lies a possible relation in the average duration of maternity care assistance and the midwives' satisfaction with collaboration with MCA(O)s on the level of urbanisation in our study. Our study did not find predicted associations of satisfaction with collaboration with attitudes towards work, such as job satisfaction, turnover intentions or retention (Baggs and Ryan, 1990;Chang et al, 2009;Anthoine et al, 2014;Zhang et al, 2016). Instead, we found differences on work-related and personal characteristics with some care providers, on the level of urbanisation, region, age, working years, non-Dutch origin and problems of accessibility in the interaction.…”
Section: Synopsiscontrasting
confidence: 95%
“…Dutch maternity care provides a unique research arena. International research shows important associations of satisfaction with collaboration and: a) work-related and personal characteristics, such as gender, race, advanced education and profession (Bruner et al, 2011) and b) attitudes towards work, such as job satisfaction (Baggs and Ryan, 1990;Chang et al, 2009;Anthoine et al, 2014;Zhang et al, 2016) and turnover intentions (Anthoine et al, 2014) or retention (Baggs and Ryan, 1990;Zhang et al, 2016). Yet, prior quantitative studies on associations with 'satisfaction with collaboration' have often focused on the physician-nurse collaboration in hospitals.…”
mentioning
confidence: 99%
“…The inclusion criteria for both the pilot and main studies were that participants were at least 18 years of age, were enrolled in an undergraduate nursing program and were full-time students during the academic year of 2020 after the COVID-19 pandemic breakout. Although there is no gold standard, the recommended sample size to validate a newly developed instrument is a minimum of five individuals per item [ 23 , 24 ]. Therefore, at least 170 participants were required for the 34-item KAP COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…Research has also shown that there are differences in the way the individual professionals construe, use, and communicate professional knowledge (Fenwick & Nerland, ), which can be a challenge for interprofessional collaboration. The reasons for these diversities can be different work responsibilities, social status or culture, and different competencies (Anthoine, Delmas, Coutherut, & Moret, ). In a literature review about the role of nursing assistants, Munn, Tufanaru, and Aromataris () summarize that there is an ambiguity regarding the roles and tasks that they fill in current health care system, especially in relation to the role and tasks of registered nurses.…”
Section: Introductionmentioning
confidence: 99%